Cover Image - Soos, Michael P. (Clin Case Rep, 2019)
The cover image is based on the Case Report Blue‐green neutrophilic inclusion bodies in the critically ill patient by Michael P. Soos et al., DOI: 10.1002/ccr3.2196. [Image: see text]